SCREENING OF HEPATITIS G AND EPSTEIN-BARR VIRUSES AMONG VOLUNTARY NON REMUNERATED BLOOD DONORS (VNRBD) IN BURKINA FASO, WEST AFRICA - Issoufou Tao; Cyrille Bisseye; Bolni Marius Nagalo; Jacques Simpore (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
In most sub-Saharan countries screening of blood-transmitted infections includes mainly HIV, HBV, HCV and syphilis. Many viruses such as Hepatitis G (HGV) and Epstein-Barr virus (EBV) which also carry a risk of transmission by blood transfusion raise the question of the extent of screening for these pathogens. This work aims to evaluate the prevalence of HGV and EBV in first-time blood donors in Ouagadougou. The prevalence of HGV and EBV in 551 blood donors was 7.4% and 5.4% respectively. HGV prevalence was significantly higher in blood donors with hepatitis B antigens and positive for HCV compared to donors negative for HCV and no hepatitis B antigens (respectively p<0.001 and p=0.004). EBV prevalence was higher among blood donors of < 20 years age group. This study shows significant results with regard to the prevalence of HGV and EBV prevalence in blood donors in Burkina Faso and emphasizes the need for a general screening.